West Bank and Gaza : Public Expenditure and Financial Accountability - World Bank (Washington, DC, 2013)
The purpose of the Public Expenditure and Financial Accountability (PEFA) assessment is to review the performance of the Palestinian Authority's (PA's) Public Financial Management (PFM) framework. The assessment examines progress since an informal PEFA assessment in 2007 and provides a baseline for supporting the PA in refining, where necessary, the current PFM reform strategy. The assessment has been undertaken following the PEFA performance measurement framework methodology as revised in January 2011. The assessment builds on previous reports by the World Bank and the International Monetary Fund (IMF) on various aspects of the PA's PFM system. The assessment is based on publicly available documents and supplementary information provided by the PA and other stakeholders. These include annual budget documents, annual fiscal outturn reports, and specific reports produced by various stakeholders. The scope of the assessment includes the Public Financial Management of the central government, the subnational government (municipalities and community villages), and the autonomous public entities which are all under the umbrella of the Palestinian investment fund. The PA was established in 1994 following the 1993 Oslo agreement, with responsibility for the West Bank and Gaza (WBG) under Palestinian control. The PA has adopted a PFM model which broadly follows the Anglophone model, but in the years following its establishment, authority has increasingly become concentrated in the executive branch and the role of parliament has been reduced. The current PEFA assessment outlines a strong link between the various reforms that require a more integrated technical assistance approach. Many of these reforms are to be implemented together with other interconnected reforms in order to produce effective results. This underscores the challenging context, in which these reforms have to be implemented, but also the opportunity to create synergy and impetus between, and ownership of, the various components of the reform agenda.